COMPARATIVE ANALYSIS OF KNEE FUNCTION AFTER TOTAL KNEE REPLACEMENT USING POSTERIOR-STABILIZED VERSUS CRUCIATE-RETAINING PROSTHESIS - Dr Pramod G; Dr Umashankar K; Dr Prakash Savakkanavar (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Total Knee Replacement (TKR) is still viewed as one of the most effective orthopedic procedures for end-stage knee osteoarthritis. The decision to implant either a posterior-stabilized (PS) design, or a cruciate-retaining (CR) design, continues to be a topic of discussion. While CR prosthesis try to maintain some or all of the posterior cruciate ligament (PCL) in order to try and restore normal gait, PS prosthesis are designed to provide rollback and stability using a cam-post device, effectively replacing the PCL altogether. These differences in design philosophy may have a significant impact on postoperative knee function and range of motion (ROM) and could be a significant factor in patient satisfaction and clinical outcomes.Objective: For the purpose of comparing functional outcomes, range of motion, and patient-reported satisfaction after total knee replacement (TKR) with a posterior-stabilized (PS) and cruciate-retaining (CR) prosthesis.Methods: We performed a prospective comparative study of 100 patients with primary osteoarthritis undergoing unilateral TKR. Fifty received a PS prosthesis and fifty received a CR prosthesis. All TKR procedures were performed for patients by the same surgical team using a standardized midline incision and medial parapatellar approach. All patients functional evaluations were performed preoperatively and at 3 months, 6 months, and 12 months postoperatively using the Knee Society Score (KSS), the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), and a visual analog scale (VAS) for pain. Radiographic evaluation assessed mechanical axis restoration and component positioning. Statistical analysis was performed with independent t-tests and paired comparisons (statistical significance p < 0.05).Results: Postoperatively, both groups showed statistically significant improvements in both KSS and WOMAC scores. The posterior-stabilized group demonstrated a slightly greater mean flexion range (118.2° ± 9.3°) than the cruciate-retaining group (112.6° ± 8.7°; p = 0.03). The mean postoperative KSS functional score was higher in the PS group (88.4 ± 6.1) compared to the CR group (84.7 ± 6.9; p = 0.04). Difference between the WOMAC and VAS pain scores at 12 months were not statistically significant in the PS and CR groups. Radiographic parameters and complication rates were similar between the two groups, indicating they had similar mechanical alignment, positioning, and placement of the implants.Conclusion: Posterior-stabilized and cruciate-retaining total knee prosthesis offer great pain relief and functional recovery. Posterior-stabilized prosthesis may provide slight advantage in terms of postoperative range of motion and function, probably owing to more consistent rollback mechanics, whereas cruciate retaining design preserves gait motion more physiologically. The decision-making for total knee prosthesis design should be individualized considering ligamentous stability, deformity, and surgeon experience.